Countermeasures under the Agreement on Subsidies and Countervailing Measures: Between the Aircraft Manufacturing Industry and Society - Ida Bagus Mahawira Nawagani; Prita Amalia; Helitha Novianty Muchtar (Udayana Journal of Law and Culture, 2021)
Countermeasures under World Trade Organization (WTO) law are separated into two categories, remedies and a method to induce compliance after another defaulting state fails to adhere to WTO's panel recommendation. This article will focus on the second category. The term ‘countermeasures’ specifically refers to an act of suspension of concessions or other obligations. One case of granted countermeasures is DS316, a case between the United States of America (US) and the European Union (EU). The issue of this case is the subsidies granted by the EU for Airbus, an aircraft manufacturer based in Europe which consists of four European nations, which resulted in Boeing's market loss. The US then requested countermeasures authorisation by the WTO. Countermeasures are related to the principle of proportionality both under public international law and WTO law. Additionally, countermeasures can lead to a more complex situation since it affects the human rights of the private actors of international trade as a part of society. This article explains the implementation of both the countermeasures and the proportionality principle, and analyses the precedents of cases and the countermeasures granted by the WTO as well as the effects of the granted countermeasures to society as it creates barriers for all the international trade actors.